Cover crops and their erosion-reducing effects during concentrated flow erosion - De Baets, S.; Poesen, J.; Meersmans, J.; Serlet, L. (Catena (Giessen), 2011)
Cover crops are a very effective erosion control and environmental conservation technique. When cover crops freeze at the beginning of the winter period, the above-ground biomass becomes less effective in protecting the soil from water erosion, but roots can still play an important role in improving soil strength. However, information on root properties of common cover crops growing in temperate climates (e.g. Sinapis alba (white mustard), Phacelia tanacetifoli (phacelia), Lolium perenne (ryegrass), Avena sativa (oats), Secale cereale (rye), Raphanus sativus subsp . oleiferus (fodder radish)) is very scarce. Therefore, root density distribution with soil depth and the erosion-reducing effect of these cover crops during concentrated flow erosion were assessed by conducting root auger measurements and controlled concentrated flow experiments with 0.1 m topsoil samples. The results indicate that root density of the studied cover crops ranges between 1.02 for phacelia and 2.95 kg m − 3 for ryegrass. Cover crops with thick roots (e.g. white mustard and fodder radish) are less effective than cover crops with fine-branched roots (e.g. ryegrass and rye) in preventing soil losses by concentrated flow erosion. Moreover, after frost, the erosion-reducing potential of phacelia and oats roots decreased. Amoeba diagrams, taking into account both below-ground and above-ground plant characteristics, identified ryegrass, rye, oats and white mustard as the most suitable species for controlling concentrated flow erosion. ►Roots increase the resistance of topsoils to concentrated flow erosion. ►Fine-branched roots are most effective in preventing concentrated flow erosion. ►After frost, the erosion-reducing potential of some species decreased. ►Fine-branched root systems (such as ryegrass and rye) are less vulnerable to frost. ►Ryegrass, rye, oats and white mustard are suitable cover crops to prevent concentrated flow erosion.